PENERAPAN METODE DISKUSI KOLABORATIF DAN TANYA JAWAB UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK PADA PEMBELAJARAN SEJARAH DI SMAN PLUS PROVINSI RIAU - Al Fiqri, Yanuar; Elfidayati, Elfidayati; Hasibuan, Halimatussakdiah; Putri, Lilis Suryani (Universitas Muhammadiyah Palembang, 2023)
This article is a scientific writing based on a simple study of two learning methods associated with the use of observational methods at sman plus riau province. The study was based on a preliminary observation of the study activity at sman plus province of riau that was still less active during the study. This is because the selection of poorly fitted learning methods with modern students. The purpose of this study is to increase student learning activity to achieve expected results. This study is consistent with the goal of Indonesian national education to shape the entire Indonesian nation, not only in terms of learning outcomes alone, but also in terms of the process of achieving learning outcomes. Collaborative learning methods are used to optimize the learning process in a way that also affects student learning outcomes. The choice of discussion and question-and-answer methods meets the 2013 Curriculum requirements for the active role of the student and the role of the teacher as a facilitator and companion in learning. The subject of this study X class, 2022/2023 academic year. Research suggests that these collaborations can have considerable impact on increasing students' activities in learning.